Constipation in children: incidence, causes in relation to diet pattern and psychosocial aspects - Kondapalli, Chandra Sekhar; Gullapalli, Sagari (International Journal of Contemporary Pediatrics, 2017)
Background: The present study was conducted to study the incidence of constipation in children attending the paediatric Op and also to know the bowel pattern in constipated children and normal children with respect to food habits and regarding psychosocial aspect of toileting. Methods: A study was done at Katuri Medical College and Hospital in 654 children with age group of 2-12yr of either sex. Children who fulfilled the ROME III criteria for constipation were analysed for demographic profile, socio-economic status, psychosocial aspects and dietary habits affecting bowel pattern. Data was collected and recorded from the parents in pre-fixed proforma. Stool frequency and type of stool passed was recorded for a week, with Bristol stool chart. Children in the study group without constipation were analyzed in similar pattern. Results: A total of 654 children were analysed, out of which 202 children fulfilled the ROME III criteria for functional constipation. The prevalence of functional constipation was noted in 30.8% with female preponderance and incidence is more in the age group of2-4 years. In children without constipation, the average number of stools passed per day is 1.342 and the predominant type of stool is Type iv. Conclusions: Constipation continues to be a problem, mostly under recognised in older population. Psychosocial factors had a significant effect on functional constipation. Skipping breakfast, early toilet practising, low intake of vegetables and fruits were other factors leading to constipation.